Analysis and Mitigation of Strategic Risk Business Process by Considering Relationship Between Risk Case Study in Electricity Generation Companies - Lalu Bramantias Gutama; I Nyoman Pujawan (Institut Teknologi Sepuluh Nopember, 2019)
In this study an analysis of the linkages between the causes of strategic risks of business processes which refers to the balance scorecard perspective in company X one of electricity generation company. Where at the initial stage prioritization of 87 risk causes identified at the outset using the House of Risk 1 method and the Pareto principle so that 17 dominant risk causes were obtained, which were then analyzed using the ISM method and then weighted using the analytic network process (ANP) method to obtain the new ARP value causes risk that has accommodated the relationship between the causes of risk.To make it easier for companies to prioritize the handling of the 17 risk-causing agents, a mitigation analysis is then carried out using the House of Risk 2 by considering the ranking of existing Effectiveness to Difficulty so that 8 strategies for handling agents that cause risk are considered effective was chosen.